The positive impact of task familiarity, risk propensity, and need for cognition on observed timing decisions in a security game - David Reitter; Jens Grossklags (Games, 2019)
This paper addresses the role of personality characteristics in decisions on the timing of an action, such as in the context of security and safety choices. Examples of such decisions include when to check log files for intruders and when to monitor financial accounts for fraud or errors. Two behavioral studies (n = 461) are conducted. Individual risk propensity and need for cognition are obtained via scales. The task is a game against an opaque computer opponent in which participants make decisions about the timing of actions in response to an unknown external risk factor. The task is not payoff-neutral w.r.t. risk. Difficulty is varied through the availability of explicitly given or decision-critical information, which is observable visually (Study 1) or in temporal memory (Study 2). Across this problem space, we find that risk propensity is not generally a hindrance in timing tasks. Participants of average risk propensity generally benefit from a high need for cognition, particularly when externalized memory is available, as in Study 1. In the more difficult temporal-estimation task, need for cognition was associated with increased payoffs from task experience. In both tasks, higher risk propensity in participants was associated with increased improvements in payoffs from task experience.
Keywords: 330; behavioral experiment; games of timing; individual differences; games of timing